PHENOTYPIC DIVERSITY AMONG INDIGENOUS COCKFIGHTING (ASEEL) CHICKENS FROM PAKISTAN - S. Mahmood; A. U. Rehman; M. S. Khan; R. A. Lawal; O. Hanotte (Journal of Animal and Plant Sciences, 2017)
Cockfighting chickens are popular in Pakistan for their fighting behavior, good quality meat and as an attractive household bird. In this study, a total of 195 cockfighting chickens were evaluated for their morphological data during August 2013 to September 2014. Morphological data of cockfighting chickens were obtained from six regions of Pakistan including Sindh, Punjab, Khyber Pakhtunkhwa, Gilgit Baltistan, Federally Administrated Tribal Areas and Azad Jammu and Kashmir. The data were analysed statistically using ANOVA test. Aseel chicken varieties in this study were characterized by red, black, white, and wheaten  plumage; yellow and brown shank; yellow beak with black patches; small earlobes; pea comb; yellow eye color and minimal wattles. Great diversity with respect to plumage was witnessed among these varieties. Mianwali Aseel showed significantly lower (p≤0.05) estimates of mean body weight and body circumference than all other studied varieties. Contrastingly, Kulung and Sindhi varieties showed significantly higher estimates (p≤0.05) of mean body weight compared to Mianwali, Mushka, Lakha, Java and Peshawari. Mean breast widths, keel lengths, pelvis lengths and body circumferences did not showed any significant difference (p≥0.05) among the studied varieties. Interestingly, Mianwali Aseel showed significantly higher estimates of mean drum length than Mushka, Sindhi, Kulung and Peshawari Aseels.Thus, we observed great phenotypic diversity among Pakistani cockfighting chickens.
Keywords: Aseel Chickens; cockfighting; Pakistan; Phenotypic diversity